ANALISIS YURIDIS ATAS IMPLEMENTASI PENDAFTARAN PERSEKUTUAN KOMANDITER (COMMANDITAIRE VENNOTSCHAP) SECARA ONLINE MENURUT PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 17 TAHUN 2018 TENTANG PENDAFTARAN PERSEKUTUAN KOMANDITER, PERSEKUTUAN FIRMA, DAN PE - SRI RUMADA SIHITE (PREMISE LAW JURNAL, 2019)
Dosen pembimbing:1. Prof. Dr. Bismar Nasution, SH, MH2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Suprayitno, SH, MKn The issuance of PP (Government Regulation) No. 24/2018 on Electronic Integrated Business Permit is based on the Decree of the Minister of Law and Human Rights No. 17/2018 on Registration of Limited Partnership, Firm Partnership, and Partnership which is aimed to develop administrative order. The research problems are how about the consideration of the Minister of Law and the Decree of the Minister of Law and Human Rights No. 17/2018 on Registration of Limited Partnership, Firm Partnership, and Partnership Human Rights in issuing the Decree No. 172018 on Registration of Limited Partnership, Firm Partnership, and Partnership, how about the role of a Notary in the process of registration, and how about its implementation. The research used juridical normative and empirical approach, and its nature was descriptive analytic. The data were analyzed qualitatively by analyzing legal provisions and using deductive method: from general to specific.Keywords: Implementation, Business Administrative System, Online Single Submission System.